The Application of Quality Function Deployment (QFD) Towards The Design of Batik Coloring Machines to Increase The Value of Fading and Stains on Fabrics - Siswiyanti, S; Rusnoto, R; Luthfianto, Saufik; Nurjanah, N (Muhammadiyah University Press, 2019)
The aim of this study is to design a batik coloring machine using the Quality Function Deployment (QFD) method in order to increase the value of fading and stains on fabrics. It can be concluded that the results of the design of batik coloring machines according to the application of QFD have 3 rollers/cylinders and propulsion about 0.190 HP with the working concept of a sheet of cloth wrapped around the cylinder with rotation of 72.5 rpm. There are significant differences between variables in the design before and after the experiment on the batik value quality analysis of soap washing and desecration of unbleached plain cloth of Primisima type, Gamelan stamp. The average difference between before and after the experiment is 0.060 or increase to 6%, while for the analysis of batik quality test, the value of rubbing dry and wet cloth has a mean difference between before and after the experiment of 0.100 or an increase of 10%. Standard time generated from the measurement process using a machine dipping carried out by 20 batik makers has a value of 0.2701 hours/ unit with total output of 4 units/ hour, while standard time for coloring activities that uses a bucket dip is 0.5346 hours / unit with total output of 2 units/ hour.